2014
DOI: 10.1136/gutjnl-2014-306997
|View full text |Cite
|
Sign up to set email alerts
|

Impact of common risk factors of fibrosis progression in chronic hepatitis C

Abstract: Most factors accelerating liver fibrosis progression in chronic hepatitis C are unmodifiable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 43 publications
3
79
1
Order By: Relevance
“…The stronger effect of PNPLA3 in non-obese patients fits with a recent study showing that the amount of liver fat is similar in obese NAFLD compared to PNPLA3 rs738409 G-associated NAFLD. Our data confirmed the link reported in CHC between the severity of steatosis and the PNPLA3 rs738409 G variant, [8][9][10][11][12][13][14][15] but we were unable to confirm a direct association with the severity of fibrosis. Differences in clinical, metabolic and histological characteristics of studied populations, as well as in the analysis of data could explain this difference.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The stronger effect of PNPLA3 in non-obese patients fits with a recent study showing that the amount of liver fat is similar in obese NAFLD compared to PNPLA3 rs738409 G-associated NAFLD. Our data confirmed the link reported in CHC between the severity of steatosis and the PNPLA3 rs738409 G variant, [8][9][10][11][12][13][14][15] but we were unable to confirm a direct association with the severity of fibrosis. Differences in clinical, metabolic and histological characteristics of studied populations, as well as in the analysis of data could explain this difference.…”
Section: Discussionsupporting
confidence: 68%
“…[5][6][7] Some studies on cohorts of mostly genotype 1 (G1) chronic hepatitis C (CHC) patients have reported an association between the PNPLA3 rs738409 G variant and the severity of both steatosis and fibrosis, the risk of fibrosis progression and HCC occurrence, and the response to pegylated interferon plus ribavirin therapy. [8][9][10][11][12][13][14][15] Bedossa et al, in liver biopsies from CHC patients, recently characterised the presence of histological features of steatohepatitis, showing that the occurrence of NASH in this setting not only was related to a poor atrisk metabolic profile but was also a risk factor for the severity of liver damage. 16 This study however did not investigate the impact of genetic background on the presence of steatohepatitis in the context of CHC.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by us indicates that this is also the case for liver fibrosis. Thus, a significant portion of the fibrosis progression rate could not be explained by common cofactors including clinical variables and SNPs discovered by GWAS, based on a low pseudo-R 2 of the multivariate logistic regression model of fibrosis progression [114]. This observation indicates that there are additional loci affecting liver injury that remain to be uncovered even after the GWAS era.…”
Section: Genes and Host-virus Interactions: Open Questions And Challementioning
confidence: 94%
“…The initial association between MERTK rs4374383 and development of fibrosis in chronic HCV disease was observed in a GWAS; in this study, the association was observed only in a sub-group of HCV patients who received blood transfusions [12]. Later, the MERTK SNP significantly added risk to accelerated fibrosis progression rate in the Swiss Hepatitis C Cohort Study [10]. Interestingly, a recent study also showed that the rs4374383 AA genotype was protective against F2-F4 fibrosis in patients with NAFLD [32].…”
Section: Discussionmentioning
confidence: 89%
“…26 No 1: 37-43 that the patatin-like phospholipase domain containing 3 (PNPLA3) gene polymorphism rs738409 was associated with NAFLD [8] and affects the activities of liver enzymes in plasma [9]. The PNPLA3 gene polymorphism rs738409 was also shown to accelerate liver fibrosis progression rate in HCV-infected patients [10] and contribute to the development of alcoholic liver cirrhosis [11]. Further genetic association studies discovered two other loci harboring RNF7, which is also known as SAG (sensitive to apoptosis gene), and proto-oncogene tyrosine-protein kinase MER (MERTK), which may influence the development of fibrosis in chronic hepatitis C [12].…”
Section: Introductionmentioning
confidence: 99%